Micro-costing analysis from Italian Guidelines for the management of sporadic primary hyperparathyroidism - Ilaria Valentini; Michele Basile; Fabio Vescini; Giorgio Borretta; Iacopo Chiodini; Marco Boniardi; Marina Carotti; Elena Castellano; Cristiana Cipriani; Cristina Eller-Vainicher; Sandro Giannini; Maurizio Iacobone; et al. (Global & Regional Health Technology Assessment)
Introduction: Primary hyperparathyroidism (PHPT) is a common endocrine disorder, primarily caused by single adenomas or multiglandular disease. This study evaluates the economic impact of different PHPT treatment approaches from both the Italian National Health Service and societal perspectives. Methods: A micro-costing approach was used to estimate the costs of surgical and non-surgical treatments. Data were gathered through a survey among panel members responsible for the Italian PHPT treatment guidelines, ensuring alignment with national clinical practice. The survey examined various cost components, including diagnostic tests, pre-hospitalization assessments, surgery duration, drug use, healthcare professionals involved, disposable materials, and follow-up care requirements. Results: The total cost for PHPT diagnosis and comorbidity assessment is € 887.96. Parathyroidectomy (PTX) costs € 4,588.00. Non-surgical alternatives, including pharmacological treatment (€ 953.34 annually) and active surveillance (€ 197.42 annually), result in cumulative 30-year costs of € 28,590 and € 5,910, respectively. Since PTX is typically performed at age 55, pharmacological treatment over 30 years incurs an additional € 22,876 per patient compared to surgery. Conclusions: Despite its higher upfront cost, PTX demonstrated long-term cost efficiency due to the relatively low rates of follow-up complications and the absence of recurring annual costs associated with conservative strategies.